The Effect of Principals’ Instructional Leadership and Teacher Learning Communities on Learning Quality in Elementary Schools - Ratna Kusuma Ningrum; Widya Kusumaningsih; Joko Sulianto (Papanda Publisher, 2026)
Learning quality in primary schools is shaped by multiple institutional factors, yet the combined influence of principals' instructional leadership and teacher learning communities remains empirically underexplored, particularly in Indonesian elementary school contexts. This study employed a quantitative correlational survey design involving 92 teachers selected through proportional random sampling from public elementary schools in Gubug District, Grobogan Regency, Central Java, Indonesia. Data were collected using three validated questionnaires measuring instructional leadership, learning community activities, and learning quality, and were analysed through multiple linear regression. Results indicate that instructional leadership significantly predicts learning quality (β = 0.512, R² = 0.279, p < 0.001), as does learning community activities (β = 0.467, R² = 0.247, p < 0.001). Crucially, their simultaneous effect accounts for 46.8% of the variance in learning quality (F(2,89) = 41.93, p < 0.001), substantially exceeding either variable's independent contribution. These findings demonstrate that instructional leadership and professional learning communities operate synergistically rather than additively, positioning principal-led direction as a structural precondition for productive teacher collaboration. Schools seeking to improve instructional quality should therefore develop both components in an integrated and sustained manner.